2015
DOI: 10.1080/2162402x.2015.1100793
|View full text |Cite
|
Sign up to set email alerts
|

Rapid dissemination of RET-transgene-driven melanoma in the presence of non-obese diabetic alleles: Critical roles of Dectin-1 and Nitric-oxide synthase type 2

Abstract: Mice transgenic for the RET oncogene provide a remarkable model for investigating the mechanisms underlying the promotion and the development of melanoma. This model was established on the C57BL/ 6 genetic background. In the present study, we investigated an effect of the strongly proinflammatory and autoimmune genetic makeup of the non-obese diabetic (NOD) strain. We bred (NODxB6)F1 mice and backcrossed them with NOD mice. F1 mice and mice at subsequent generations of backcrossing showed marked acceleration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In Ret mice with a NOD genetic background, we have shown that the rapid tumor cell dissemination strongly correlates with a reduced dectin-1 expression on myeloid cells that is prevented by NOS2 inactivation. 24 Here, we observed that RetNos2KO mice with C57Bl/6J genetic background survived better than Ret mice owing to the significant delay of tumor cell dissemination, despite a comparable primary tumor incidence in 6-mo-old animals. Our previous demonstration supported the key contribution of PMN-MDSCs in tumor cell dissemination in the Ret model.…”
Section: Discussionmentioning
confidence: 79%
“…In Ret mice with a NOD genetic background, we have shown that the rapid tumor cell dissemination strongly correlates with a reduced dectin-1 expression on myeloid cells that is prevented by NOS2 inactivation. 24 Here, we observed that RetNos2KO mice with C57Bl/6J genetic background survived better than Ret mice owing to the significant delay of tumor cell dissemination, despite a comparable primary tumor incidence in 6-mo-old animals. Our previous demonstration supported the key contribution of PMN-MDSCs in tumor cell dissemination in the Ret model.…”
Section: Discussionmentioning
confidence: 79%
“…IFN-γ-inducible nitric oxide synthase (Nos2) was involved in inflammation and accelerated tumorigenesis. These data point to a role of inflammation in UM development and to dectin-1 and Nos2 as potential therapeutic targets [395]. …”
Section: Animal Modelsmentioning
confidence: 99%
“…MDSCs inhibit T-cell function in melanoma both at the tumor itself and peripheral lymphoid organs [49]. In the RET (REearranged during Transfection) transgenic murine melanoma model, NOS2 expression was associated with increased MDSC recruitment by IL-12 producing γδ T cells and activation of T regulatory cells [57, 58]. VEGF secretion in the tumor microenvironment via iNOS dependent mechanisms also led to the recruitment of MDSC [59].…”
Section: Mechanisms Of Nitric Oxide Production In Melanomamentioning
confidence: 99%